2008
DOI: 10.1016/j.visres.2008.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Gender-selective effects of the P300 and N400 components of the visual evoked potential

Abstract: There is an ongoing controversy regarding the role of gender in modulating components of the human visual-evoked potential (VEP) and event-related potentials (ERPs). Our aim was to further characterize the role of gender on VEPs, ERPs and response performance in an object recognition task. We recorded VEPs and reaction time (RT) in a paradigm wherein subjects responded to a randomly presented "Relevant" stimulus, and did not respond when presented with "Irrelevant" or "Standard" visual stimuli. There was no ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 62 publications
7
41
2
Order By: Relevance
“…Similarly, correlations between P300 amplitudes and callosal morphology emphasize the relevance of interhemispheric interactions for this ERP. One has to stress that the sex-related differences reported here go well beyond those effects that have been reported earlier (e.g., Steffensen et al 2008;Conroy and Polich 2007;Yuan et al 2008), which usually indicate higher ERP amplitudes with female subjects. However, these kinds of sex differences can be explained in terms of variations in head size and geometry only, without necessarily denoting any essential functional relevance.…”
Section: Discussionsupporting
confidence: 50%
“…Similarly, correlations between P300 amplitudes and callosal morphology emphasize the relevance of interhemispheric interactions for this ERP. One has to stress that the sex-related differences reported here go well beyond those effects that have been reported earlier (e.g., Steffensen et al 2008;Conroy and Polich 2007;Yuan et al 2008), which usually indicate higher ERP amplitudes with female subjects. However, these kinds of sex differences can be explained in terms of variations in head size and geometry only, without necessarily denoting any essential functional relevance.…”
Section: Discussionsupporting
confidence: 50%
“…alpha, gamma) are sensitive to the top-down effects of selective attention (Hermann & Knight, 2001;Katayama & Polich, 1998 Moreover, recent evidence has shown attention-related sex differences in neural activity occur in the visual cortex (Steffensen et al, 2008), and to a somewhat lesser extent, in the somatosensory cortex (Cheng et al, 2006;Cheng et al, 2008a, Yang et al, 2009 (Cheng et al, 2006;Cheng et al, 2008, Cheng et al, 2008b have suggested that sex differences in neural activity patterns may reflect sex-specific cognitive strategies.…”
Section: Section Iii: Rationale For My Studymentioning
confidence: 99%
“…Growing evidence suggests that there are measurable differences in how males and females selectively direct their attention to sensory stimuli (Neuhaus et al, 2009;Ruytiens et al, 2007;Steffensen et al, 2008). For example, a recent electroencephalography (EEG) study found sex differences of the visual evoked potential during a self-directed attention task, which suggested that females may process visual information in a more effortful manner than males by allocating more attentional resources to distracting stimuli (Steffensen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they did not consider the effect of age accurately. Steffensen et al (2008) showed that females have greater P300 responses than males [7]. However, their investigation was conducted with the use of visual stimuli.…”
mentioning
confidence: 99%